Analisis Faktor Penyebab Ketidaktercapaian Target Kredit Usaha Rakyat di Bank Tabungan Negara Cabang Magelang - Denise Sekarsari Suyatno; Utpala Rani; Kartika Pradana Suryatimur (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
KUR is a program that is in great demand by the community, especially those who have entrepreneurs. Bank BTN Magelang branch has a KUR program but for the last 3 years it has not been able to achieve the target set. The purpose of this study was to identify the factors that caused the non-achievement of targets in the People's Business Credit (KUR) program at the Magelang branch of BTN. This research method is descriptive qualitative, using primary data obtained directly from interviews with related field implementers and indirectly through related document reports. The results of the research conducted indicate that the business process of the People's Business Credit (KUR) program at the Magelang branch of bank BTN goes through several interrelated stages, namely marketing, surveys or OTS (On-The Spot), credit analysis and proposals, documentation and administration, contracts. and disbursement, monitoring, and evaluation. In the program, there are several factors that caused the target not to be achieved, including the lack of competent human resources for implementing the KUR program system, non-optimization of the KUR program system, and unqualified customers causing delays in the KUR process.